Strategi Komunikasi Pemerintah Dalam Meningkatkan Partisipasi Masyarakat Pada Program Pembangunan di Kelurahan Karawang Kulon - Putri, Zahra Avilya; Priyanti, Evi (Universitas Muhammadiyah Sumatera Utara, 2024)
This research explains the government's communication strategy in increasing community participation in development programs in Karawang Kulon Village. Using Harold Lasswell's theoretical approach which considers five elements of communication, this research analyzes the role of government as a communicator, message formulation, media used, public perceptions and attitudes, as well as responses to government messages. The research method used is a qualitative study with a focus on direct interactions between the government and the community, as well as evaluating the community's response to the messages conveyed. The results of the analysis show that inclusive and open communication strategies play a key role in motivating active community participation in local development. The people of Karawang Kulon show a high level of participation and a positive response to government efforts, reflecting close cooperation between the government and the community in achieving better development goals. The implication of this research is the importance of developing effective and inclusive communication strategies in strengthening relations between government and society, as well as increasing community participation in development programs.Keywords: strategy, communication, government, development, community participation